1985
DOI: 10.1677/joe.0.1040211
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and vasopressin in rat hypophysial portal blood: experimental studies in normal and Brattleboro rats

Abstract: Oxytocin (OT) and vasopressin (VP) were measured by radioimmunoassay in hypophysial portal and peripheral blood from male Wistar rats and heterozygous and homozygous Brattleboro rats anaesthetized with urethane. In Wistar rats the concentrations of OT and VP were about 50 times greater than the concentrations in peripheral blood, whether or not the pituitary gland was left in situ during collection, and also considerably greater than the reported concentrations of the peptides in the cerebrospinal fluid. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

1986
1986
1993
1993

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 55 publications
3
55
1
2
Order By: Relevance
“…Basal resting intracellular calcium levels were stable and Addition of OT (100 nM) increased the cytosolic free calcium concentrations to values ranging from 500-800 nM in 30 (of 32) identitied corticotrophs. Increased intracellular calcium was evident within 3 sec, then declined in [10][11][12][13][14][15] sec toward a plateau slightly higher than the calcium concentration observed underresting conditions (Fig. 6A).…”
Section: Changes In Intracellular Free Calcium Concentration Caused Bmentioning
confidence: 72%
See 1 more Smart Citation
“…Basal resting intracellular calcium levels were stable and Addition of OT (100 nM) increased the cytosolic free calcium concentrations to values ranging from 500-800 nM in 30 (of 32) identitied corticotrophs. Increased intracellular calcium was evident within 3 sec, then declined in [10][11][12][13][14][15] sec toward a plateau slightly higher than the calcium concentration observed underresting conditions (Fig. 6A).…”
Section: Changes In Intracellular Free Calcium Concentration Caused Bmentioning
confidence: 72%
“…In addition, CRF-, AVP-and OT-containing neurons in the hypothalamic paraventricular and supraoptic nuclei project to the median eminence and release these peptides into hypophyseal portal blood (8)(9)(10). Here, the concentration ofthese peptides are several times greater compared to peripheral blood (11)(12)(13)(14)(15). Thus, OT as apart of this hypophysiotropic cocktail in the adenohypophyseal circulation could contribute to physiological regulation of ACTH secretion by the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Using the transpharengeal or parapharengeal approach, several groups of investigators have also obtained 20-to 50-fold higher concentrations of OT in pituitary portal plasma than in peripheral plasma in male and female rats. 22,40,[43][44][45] It is unlikely that a significant amount of OT in pituitary portal plasma is due to backflow from the posterior pituitary gland, since the level of pituitary portal OT did not change following removal of the pituitary gland (Table 1). It has been shown that a significant amount of OT is present in the cerebrospinal fluid (CSF) and in tanycytes lining the floor of the third ventricle.…”
Section: Methodological Considerationmentioning
confidence: 99%
“…Horn et al have recently presented evidence that OT from the cut axons of the supraoptico-hypophysial tract does not significantly contribute to the high neuropeptide level in pituitary portal plasma following sectioning of the pituitary stalk. 44 Thus, the OT concentration in pituitary portal blood reflects the secretory activity of OT neurons in the median eminence.…”
Section: Methodological Considerationmentioning
confidence: 99%
“…However, recent immunoassay studies of the rats have detected hypophyseal hormones, including MSH and oxytocin, in the blood in long portal vessels (OLIvER et al, 1977 ;GIBBS, 1984;HORN et al, 1985). These studies suggest that the blood in the long, short, intra-adenohypopyseal portal vessels and the intercommunicating capillaries can return in part to the median eminence, infundibular stalk and also infundibular process.…”
Section: Discussionmentioning
confidence: 98%